Reduced Bone Mineral Density in Nigerian Women: A Prevalence Study - Njeze, Ngozi Rosemary; Agwu-Umahi, Olanike; Ezeofor, Salome Nwaelom; Arinze-Onyia, Sussan; Njeze, Nneze C.; Akpagbula, Damaris Ulugo; Madu, Kenechi (Nigerian Journal of Orthopaedics and Trauma, 2019)
Background: Reduced bone density if left untreated is a known precursor of osteoporosis, a silent disease with increased morbidity. In the developing country, fragility bone fractures occur in the general population, and health‑seeking behaviour is low. An incredibly high level of ignorance is observed. Methodology: A descriptive cross‑sectional study was carried out to determine the bone mineral density (BMD) among patients who visited a specialist clinic for screening for osteopenia using the unigamma dual energy X‑ray absorptiometry (DXA) machine. 54 participants were selected for this study having met the inclusion criteria. Data were analysed using SPSS version 22 with P = 0.05. Results: BMD of 54 women whose ages ranged 42–86 were analysed. Twenty‑eight (51.9%) were obese while 7 (13.0%) had normal weight. 50 (92.6%) had low BMD. BMD of the right and left femora correlated more with age (P = 0.015 and 0.008, respectively). Mild and severe osteopenia were found mostly in the left femoral neck and left femoral ward, respectively, while moderate osteopenia was more common in the right greater trochanter. In this population, diagnosis of loss of bone mass by DXA examination is best on the left femur. Conclusion: Reduced BMD was present in most participants. It is advised that Nigerian women have their baseline bone density test to avoid unnecessary preventable fractures later in life. More awareness programmes is advised in the future.